Nutritional Intake And Affecting Factors Of Edelry People Living At Nursing Home - Ravika Khaila Arrum; Dewi Marhaeni Diah Herawati; Lazuardi Dwipa (poltekkes kemenkes mataram, 2020)
The incidence of malnutrition in elderly at nursing homes has reached 20%. Malnutrition is caused by inadequate nutritional intake which is affected by multiple factors, including internal factors and external factors. The purpose of this study was to determine the nutritional intake and affecting factors which support nutritional intake adequacy of elderly people living at Tresna Werdha Budi Pertiwi Nursing Home. The design of study was descriptive mixed method with sequential explanatory approach. The quantitative analysis was conducted to determine the amount nutritional intake, while the qualitative analysis was performed to explore the internal and external factors which involved adequate nutritional intake of the elderly people. The subjects were 20 elderly people recruited by a total sampling method living at the Tresna Werdha Budi Pertiwi Nursing Home, who met the inclusion and exclusion criteria. The nutritional intake was assessed using 24 hours food recall by nutritionist and its comparison with the Indonesian nutrition recommendation. Meanwhile, the internal and external factors were explored through in-depth interviews . The average nutritional intake of the elderly people was insufficient to meet the RDA standards, except for vitamin A. The internal affecting factors included early satiety, xerostomia or dry mouth and poor chewing ability. The external affecting factors included unbalanced portion sizes, poor food variety and eating alone. The elderly people living at the nursing home had inadequate nutritional intake, except for vitamin A. The internal factors which had negative effects were early satiety and xerostomia, while the external factors included unbalanced portion sizes, poor food variety and eating alone.